(untitled) (Indian Journal of Public Health Research & Development, 2020)
Cervical cancer is one of the most common neoplastic diseases in women in the world. Most of the occurrences of cervical cancer occur in developing countries, so cervical cancer becomes the main cancer for women in developing countries. The presence of cervical cancer results in a decrease in the quality of life in women as sufferers. The research method was case control by looking at the data from the respondent’s medical records and analyzed using chi square and logistic reggresion. The purpose of this study was to identify the relationship between parity and the type of cervical cancer histopathology. Most respondents were aged 36-50 years and the incidence of SCC and adenocarcinoma with parity. Based on the results of univariate analysis between variables obtained p = 0.036, it can be said that parity with histopathology type is related to the strength of 0.118 and multivariate test found that 2-4 parity is more at risk of cervical cancer with histopa SCC with OR 0.037. Parity with 2-4 is the highest number in this study which suffered from squamous cell carcinoma. Educational efforts related to the program to limit the number of births.